THE INDONESIAN ARTS AND CULTURE SCHOLARSHIP AS AN INSTRUMENTALITY OF CULTURAL DIPLOMACY INDONESIA - Kurnia, Maylani (Transformasi, 2016)
Indonesia is a country that has a strategic location on the trade route, almost allcountries use that trade route which led intercorrelation about acculturation and assimilationculture that affecting each other. This also follows many problems, especially in the area whichdirectly adjacent to Indonesia. Therefore, Indonesia initiated to held some dialogues in thoseregion. South West Pacific Dialogue (SWPD) is one of the dialogue which then produces somecooperation, one of the cooperation in the field of culture, namely Indonesian Arts and CultureScholarship. Culture is a 'soft power' of Indonesia, it then utilized earnestly in order to restoreand enhance the image of Indonesia in the international world through cultural diplomacy. Thetype of research used in this paper is a qualitative research approach to literature. The dataused is secondary data. The techniques of secondary data collection used from documents whichinclude terms of reference of Indonesian Arts and Culture Scholarship from the website of theMinistry of Foreign Affairs and some supporting data of cultural diplomacy obtained by theresearcher. Data analysis techniques using three main components: data reduction, datapresentation and conclusion that accompanied by verification data by data sourcestriangulation. Based on the research results obtained by the researcher, it can be concluded thatcultural diplomacy undertaken by Government of Indonesia through the Indonesian Art andCulture Scholarship program became one of the tools of diplomacy Indonesia through theapproach of 'people to people contact'. It can be seen from the participants of Indonesian Artsand Culture Scholarship are increasingly every year. The former of Indonesian Art and CultureScholarship programcan contribute to Indonesia as a cultural ambassador of Indonesia in theirrespective countries. Then through those cultural diplomacy, Indonesia is undergoingrestoration and enhancement of its image in the international community.Keywords: Indonesian Arts and Cultural Scholarship, Cultural Diplomacy, Soft PowerDiplomacy.